Role of Msmes in Stirring The Social Economy at Bengaluru - Balakrishnan, Adhinarayanan; A R Gowda, Ashok (Universitas Dinamika, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Bangaluru is a critical contributor to the economic escalation and employment generation. This study aims to explore the issues regarding the performance and progress of MSMEs. The study is descriptive in nature, both primary and secondary data collected and appropriate statistical tools employed to draw the inherent facts about MSMEs performance. The study divulged that the MSME sector in Bengaluru faces challenges, such as access to finance, infrastructure constraints, and regulatory compliance. MSMEs rely on traditional banking channels for financing, while few look for NBFIs because of their flexible lending criteria. The future growth and prospects of MSMEs in the services industry are promising, By embracing innovation, collaboration, sustainability, talent development, market differentiation, customer-centricity, agility, resilience, continuous improvement, adoption of emerging technologies, focus on data analytics, expansion into niche markets, and adoption of flexible business models, MSMEs can unlock their full potential and grow. With the right support, resources, and strategies, MSMEs can take advantage of the growing demand for services and emerging opportunities in the digital economy.